Positioning the Tata Nano (B) - Tybout, Alice M., (SAGE knowledge. Cases., 2016)
The case focuses on positioning a new brand, the Tata Nano. The car has been widely publicized as the world's cheapest car at Rs.1 lakh. Students must consider the gap between the ultimate target, the huge emerging middle class of Indian consumers, and the limited capacity and distribution available in choosing a target. They also must select between alternative competitive frames and the various points of difference they highlight. The case unfolds in two stages. The first decision point is in 2009, at the time of the product launch. The second decision point is 18 months later, after production capacity has increased and some product safety issues have arisen.